STUDIES ON GENETIC DIVERGENCE IN PUMPKIN - M. LAKSHMAN NAIK,; V. M. PRASAD, (The Bioscan, 2015)
25 cultivars of Pumpkin are evaluated systematically during the research period. Analysis of variance studies indicates significant differences among all the genotypes for all the characters under study. Genetic diversity worked out using Mahalanobis D 2 statistic. Based on D 2 analysis, the genotypes were grouped into 5 different clusters, where the cluster V possessed higher number (8) of genotypes followed by the cluster I (5) cluster IV (5), III (3), II (2) and VI (2). Clustering pattern revealed that geographical diversity was not associated with genetic diversity. The maximum inter-cluster distance was observed between the clusters III, VI and cluster II, III that of minimum in between the Clusters V and Cluster VI. The wider genetic diversity was observed in cluster II, III and VI which indicate the potentiality of this diverse genotype collection for providing basic material for future breeding programmes.